THE IMPACT OF GENERATIVE AI–INTEGRATED TEACHING ON UNIVERSITY STUDENTS’ KEY COMPETENCIES - Min Hui Lee; Linda Lin Chin Lin (Graduate Program of Universitas Tarumanagara, 2026)
With the rapid proliferation of Generative AI (GenAI), higher education is facing a critical shift in pedagogical paradigms. This study investigates the impact of integrating GenAI tools—such as ChatGPT, Gemini, and Canva AI—into an undergraduate